Status, social norms, or safety? understanding intended and reported bottled water use in Urban Mashhad, Iran - Seyed Ahmad Mir Mohamad Tabar; Alexandra Brewis; Maryam Sohrabi (IWA Publishing, 2023)
Personal plastic-bottled water use is highly commodified, raising an array of cost and environmental concerns, and continues to grow globally. Studies in lower-income nations suggest safety as a primary motivation for such water purchases, but studies in high-income nations with greater relative affordability suggest it is more tied to socially situated consumer decisions like status and aesthetics. Here, we consider what motivates bottled water use in an urban city (Mashhad) in a middle-income predominantly Muslim country (Iran), where there is a likely intersection of safety (due to contamination), social norms, and status concerns. Surveys were collected with a random population-representative sample of resident adults from discrete households (n = 970). Structured equation modeling testing the relative effects on reported bottled water intentions and use shows that all these factors are shaping people's decisions. Both higher- and lower-income residents' responses suggest that status and social norms considerably influence intentions to use. Overall, even despite real safety issues with tap water, social norms and status concerns seem to weigh more heavily on residents' decisions to drink bottled water. HIGHLIGHTS Many residents use tap water despite contamination of ground water, especially lower income.; Bottled water is used more by women than men.; Bottled water use increased with perceived safety benefits, education, self-efficacy, income, and household size.; Status awareness and social norms notably affected bottled water use and intentions, even once safety/health concerns and income were taken into account.;